Input specificity and location - Pontes, José Pedro (2010)
In a two-region economy, two upstream firms supply an input to two consumer goods firms. For two different location patterns (site specificity and co-location of the suppliers), the firms play a three-stage game: the input suppliers select transport rates; then they choose outputs; finally the buyers select quantities of the consumer good. It is concluded that thesitespecificity of the input leads to a high transport cost and to its specialized adaptation to the needs of the local user.